Feeding behaviour of Glossina pallidipes and G. morsitans centralis on Boran cattle infected with Trypanosoma congolense or T. vivax under laboratory conditions - Moloo, S.K.; Sabwa, C.L.; Baylis, M. (Wiley, 2000)
In field studies, tsetse flies (Diptera: Glossinidae) feed more successfully on cattle infected with Trypanosoma congolense Broden (Kinetoplastida: Trypanosomatidae) than on cattle infected with T. vivax Ziemann or uninfected cattle. Here we describe the first laboratory investigation of this phenomenon. In the first experiment, caged Glossina pallidipes austen were fed for 1 and 5 min on a Boran steer infected with T. congolense clone IL 1180 and on an uninfected steer. Feeding success was recorded in this way five times over several weeks. The same protocol was subsequently used in three additional experiments with the following combinations: G. pallidipes and a steer infected with T. vivax stock IL 3913, G. morsitans centralis Machado and a steer infected with T. congolense, and G. morsitans centralis and a steer infected with T. vivax. the four experiments were replicated once, making eight experiments in total. In three experiments there was increased tsetse feeding success, measured at 1 min. after a steer became infected (T. congolense, two experiments and T. vivax, one experiment). Analysis of all data combined found no significant differences in tsetse feeding success on the different groups of cattle prior to infection, but after infection tsetse feeding success was significantly greater on the infected cattle (P<0.001). Trypanosoma congolense infection led to a greater increase in tsetse feeding success than T. vivax infection. The increase in feeding success was not related to changes in the level of anaemia, skin surface termperature or parasitaemia. A possible explanation is the effects of trypanosome infection on cutaneous vasodilation and/or blood clotting in infected cattle. When allowed to feed for 5 min, nearly all tsetse engorged successfully and effects of cattle infection on feeding success were not found.